Crash Prediction for Prioritization of Intersections for Safety Improvement: Case Study of Kathmandu Valley - Bhattarai, Sujan (Journal of Advanced College of Engineering and Management, 2019)
Every year globally 1.3 million people lose their lives from road traffic crashes (RTAs). Similarly, increasing rate of RTAs has been observed in Nepal including Kathmandu valley. This study is focused on the analysis of crash trends and respective site specific geometric features of urban road intersections in Kathmandu valley. Seventeen major intersections based on the data availability and traffic volume, are considered for the analysis of crash type. Previous crash data and traffic volume records of one year have been analysed. Common types of three and four legged intersections were taken for the study. Classified traffic volume at those intersections were converted into the Annual Average Daily Traffic. Evaluation factors for the crash analysis were determined by using predictive method. Crash frequency, crash rate, critical crash rate and crash prediction methods were used for ranking of the intersection. Priority for the safety improvement is prepared based on the results of this study.